2013
DOI: 10.1542/hpeds.2012-0058
|View full text |Cite
|
Sign up to set email alerts
|

When and How Pediatric History and Physical Diagnosis Are Taught in Medical School: A Survey of Pediatric Clerkship Directors

Abstract: This study demonstrated striking variability among MS in how and when medical students were taught PHPDS. Clarification of the role of PHPDS instruction in preclinical years and standardized effective approaches to PHPDS instruction are both needed so that MS curriculum optimizes physician training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…As undergraduate medical education (UME) pre-clinical curricula tend to highlight adult-oriented pathophysiology and clinical skills, medical students receive comparatively less and more variable exposure to pediatric content. 1 - 3 In fact, medical students are generally perceived as less prepared for the pediatric clerkship (PC), both by PC directors and by the students themselves. 4 - 7 Students therefore rely on pediatric-specific didactics delivered during the clerkship in order to supplement and solidify wards-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…As undergraduate medical education (UME) pre-clinical curricula tend to highlight adult-oriented pathophysiology and clinical skills, medical students receive comparatively less and more variable exposure to pediatric content. 1 - 3 In fact, medical students are generally perceived as less prepared for the pediatric clerkship (PC), both by PC directors and by the students themselves. 4 - 7 Students therefore rely on pediatric-specific didactics delivered during the clerkship in order to supplement and solidify wards-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, medical schools have taught a broad overview of basic sciences and clinical skills during the pre-clinical curricula. There is striking variability on how and when pediatric content and skills are taught to medical students [ 2 ]. In a previously published study, we found that more than one third of 3 rd year medical students completing their pediatric clerkship at one of four U.S. medical schools did not feel well-prepared for the clerkship [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is striking variability on how and when pediatric content and skills are taught to medical students. [2] In a previously published study, we found that more than one third of 3rd year medical students completing their pediatric clerkship at one of four U.S. medical schools did not feel wellprepared for the clerkship. [3] In addition, one third of students speci cally felt unprepared to perform pediatric physical exam skills.…”
mentioning
confidence: 99%